In silico approach in the evaluation of pro-inflammatory potential of polycyclic aromatic hydrocarbons and volatile organic compounds through binding affinity to the human toll-like receptor 4 - Cabral, Marie Beatriz D.C. (Animo Repository, 2022)
Polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs) are widespread across the globe as they exist in the environment in complex mixtures which could initiate respiratory illnesses. In this paper, the proinflammatory potential of various carcinogenic PAHs and VOCs were evaluated using an in silico approach. For the molecular docking, the structures of the ligands were obtained from PubChem, while the receptor was obtained from RCSB Protein Data Bank. Meanwhile, AutoDock Vina was utilized to obtain the best docking poses, and binding affinity value (kcal/mol) for each PAH and VOC bound to the human toll-like receptor 4 (TLR4). Indeno(1,2,3-cd)pyrene, benzo(ghi)perylene, and benzo[a]pyrene had the highest binding affinity values among the 14 PAHs studied. For the VOCs, benzene,1,4-dichlorobenzene, and styrene had the highest binding affinity with values of -3.6, -3.9, and -4.6 kcal/mol, respectively. Compounds could potentially induce inflammation if the affinities are higher than LPS (-4.1 kcal/mol), while compounds with lower affinity are less likely to cause inflammation. Statistical analysis and RMSF graphs for the molecular dynamics demonstrated that the receptor, TLR4, will maintain its structure despite ligand interactions. Overall, the structure of the TLR4 was considered inflexible. Keywords: in silico; molecular docking; molecular dynamics; TLR4; PAHs; VOCs; binding affinity; LPS